Soft Masculinity Sebagai Tren Laki-Laki Masa Kini - Latifah Sayyidah Amir; Mustiawan; Tellys Corliana (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research looks at the phenomenon of soft-masculinity in Somethinc advertisements. The advertisement represents a different concept of masculinity from traditional masculinity, which displays a softer male figure in appearance. Our research aims to describe the interpretation of the meaning of soft-masculinity as a trend for men today. The research uses a qualitative approach and semiotic analysis method of Charles Sanders Peirce model to examine the meaning contained in a reality without changing its essence. The analysis is done through observation and documentation, by interpreting the signs that appear in the object of research. This analysis focuses on five specific scenes in the advertisement that show the concept of soft-masculinity. The results confirm that there are eleven signs of soft-masculinity that undermine the meaning of traditional masculinity, namely: soft-colored clothes, looking in the mirror, wearing earrings, hair with bangs, body gestures, collar, dancing, plaint pants, taking care of the face, glowing face, and not having a mustache and beard. The results of this study conclude that advertisements try to open a space for discussion and construct a more inclusive concept of soft-masculinity, so these signs are widely used by men and have become a trend for men today. However, Indonesian society still maintains traditional masculinity. This research provides a clearer understanding of the concept of soft-masculinity.